2007
DOI: 10.1016/j.ejcnurse.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and health-related quality of life in elderly patients with and without heart failure in primary healthcare

Abstract: Elderly patients in primary healthcare with confirmed heart failure and patients with symptoms similar to heart failure perceived they had a significantly worse physical QoL and more general and physical fatigue than an age- and sex-matched control group. The similarities between the patient groups indicate the importance of the symptom experience for Hr-QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 47 publications
2
22
1
2
Order By: Relevance
“…This fi nding contrasts to a recent study in which women reported higher degrees of general fatigue and reduced activity (Hägglund et al, 2006). Women were slightly older than men and older age was associated with reduced motivation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This fi nding contrasts to a recent study in which women reported higher degrees of general fatigue and reduced activity (Hägglund et al, 2006). Women were slightly older than men and older age was associated with reduced motivation.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation means that physical fatigue has an independently strong impact on the perception of health and that both physical and mental aspects of fatigue infl uenced the QOL. The fi nding is consistent with a study showing that the general sensation of fatigue (measured with MFI-20) was signifi cantly related to lower HRQOL (Hägglund et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Physical exercises as a part of treatment of patients with heart failure promote patients' physical function and patients' promoted quality of life can be expected by decreasing fatigue level (49). Functional status should also be considered when taking care of the patients; it may be that the patient or their family needs to be trained for promoting activities.…”
Section: Discussionmentioning
confidence: 99%
“…Another frequent and distressing symptom experienced by these patient groups is fatigue,1416 which is estimated to occur in 43%–58% among patients with COPD, and in 50% among patients with CHF 16. Fatigue limits physical and psychosocial functioning in patients with COPD,17 while global and physical functioning are most affected in patients with CHF 18. Anxiety and depressive symptoms are prevalent in both patient groups.…”
Section: Introductionmentioning
confidence: 99%